Phenolic content and antioxidant activities of commercial pomegranate and date concentrates - Nur Ain Hafizah Che Malek; Hasnah Haron; Hanis Mastura Yahya (Penerbit Universiti Kebangsaan Malaysia, 2019)
The aim of this study was to determine the polyphenol content and antioxidant activities in commercialized date and pomegranate concentrates that are available in local market. A total of seven samples comprised of two brands of date concentrates (D1 and D2) and five brands of pomegranate concentrates (P1, P2, P3, P4, and P5) have been analyzed for their polyphenol content and antioxidant activity. The Folin-Ciocalteu assay was used to determine the polyphenol content (TPC) of the samples while 2,2-diphenyl-1-picrylhydrazyl-hydrate (DPPH) and Ferric Reducing Antioxidant Power (FRAP) assays were used to determine the antioxidant activity. The results showed the commercialized date concentrate D2 contained the highest TPC (1243.00 ± 67.00 mg GAE/100 ml) and antioxidant activity using FRAP assay (2.67 ± 0.01 mmol TE/100 ml). Date concentrate D1 showed the highest antioxidant activity using DPPH assay (0.39 ± 0.02 mmol TE/100 ml). The pomegranate concentrate P5 showed the highest reading for TPC (3260.10 ± 428.70 mg GAE/100 ml), DPPH (1.61 ± 0.05 mmol TE/100 ml) and FRAP assays (20.98 ± 0.42 mmol TE/100 ml). As a conclusion, the studied commercial date and pomegranate concentrates available in the local market contained high polyphenol and antioxidant contents although the content levels were different from one brand to another. Further study is needed to identify the causes of this distinction. The results of this study could help the consumers to make a better selection of commercialized date and pomegranate concentrates that are available in local market in term of polyphenol content and antioxidant activity.